Human induced pluripotent stem cells derived endothelial cells mimicking vascular inflammatory response under flow - Wang, Li (Biomicrofluidics, 2016)
Endothelial cells (ECs) have great potential in vascular diseases research and regenerative medicine. Autologous human ECs are difficult to acquire in sufficient numbers in vitro, and human induced pluripotent stem cells (iPSCs) offer unique opportunity to generate ECs for these purposes. In this work, we present a new and efficient method to simply differentiate human iPSCs into functional ECs, which can respond to physiological level of flow and inflammatory stimulation on a fabricated microdevice. The endothelial-like cells were differentiated from human iPSCs within only one week, according to the inducing development principle. The expression of endothelial progenitor and endothelial marker genes (GATA2, RUNX1, CD34, and CD31) increased on the second and fourth days after the initial inducing process. The differentiated ECs exhibited strong expression of cells-specific markers (CD31 and von Willebrand factor antibody), similar to that present in human umbilical vein endothelial cells. In addition, the hiPSC derived ECs were able to form tubular structure and respond to vascular-like flow generated on a microdevice. Furthermore, the human induced pluripotent stem cell-endothelial cells (hiPSC-ECs) pretreated with tumor necrosis factor (TNF-α) were susceptible to adhesion to human monocyte line U937 under flow condition, indicating the feasibility of this hiPSCs derived microsystem for mimicking the inflammatory response of endothelial cells under physiological and pathological process.